A Fatal Pneumonia due to Coinfection of Pseudomonas putida and Staphylococcus pseudintermedius in a Laboratory Beagle Dog - Hong, Min; Wei, Liping; Chen, Yan; Qin, Yongchang; Wang, Xin; Zhang, Yaqun; Chang, Yan; Li, Hua (Acta Scientiae Veterinariae, 2021)
Background: Pseudomonas putida (P. putida) is widely distributed in the environment, and sometimes caused nosocomial infections in human beings, but no case of infection has been reported in beagle dogs. Staphylococcus pseudintermedius (S. pseudintermedius) is a natural cutaneous bacterium in dogs and occasionally causes purulent infections of the skin and rarely causes pneumonia. Both bacteria are opportunistic pathogens. Dogs, even well-controlled laboratory beagle dogs, maybe infected by the bacterium in certain conditions like this report. In order to provide information and give suggestion to veterinarians involved in dogs study, a complete profile of the coinfection was drawn in this report. Case: It is presented a case of an 8-month-old beagle dog, weighing 6 kg that suffered from coinfection of P. putida and S. pseudintermedius during a treatment of chemotherapy. The animal was confirmed as normal by appearance, physical examination, and laboratory tests before arrival according to the applicable guidelines. After 14-day acclimation period, the animal was administrated with a tyrosinase inhibitor once daily via oral gavage. From Day 8, coughing, decreased activity, hyporeflexia, squinting, shortness of breath (abdominal breathing), and discharge around the nose as well as crackles in the lung and rapid heart rate were noted. Since the poor conditions progressed rapidly and have not been improved by treatment of ceftriaxone and dexamethasone. On Day 9, the animal was euthanized for humanitarian reasons due to rapid progress and poor condition. To define the pathogen, hilar lymph node and thoracic swab were collected for bacteria isolation and purification in special mediums, and at last characterized by Gram staining and 16s rRNA gene sequence analysis and positive PCR-restriction fragment length polymorphism. In clinical pathological examination, an increase in WBC, neutrophils, lymphocytes, monocytes, cholesterol, triglyceride, total protein, globulin, and lactate dehydrogenase, as well as a decrease in RBC, hemoglobin, hematocrit, platelets, sodium ion, chloride ion, and albumin were noted. At necropsy, dark red and enlarged lymph nodes were noted in the hilum of lung, multiple abscesses with yellow pus and multifocal hemorrhage were noted in the lung, and a large amount of frothy yellow fluid were noted in the trachea. In pathological examinations, severe neutrophilic inflammation, diffuse and moderate macrophage aggregation, mild hemorrhage, and moderate alveolar emphysema were noted in the lung, and severe sinusoidal stasis were noted in portal lymph nodes. Discussion: The current case presented a profile of the appearance, treatment, hematological examination, coagulation examination, clinical chemistry, macroscopic and histological changes in the lung. Multiple purulent abscesses, infiltration of neutrophils, macrophage, and hemorrhage, were correlated to the increase in WBC, neutrophils, lymphocytes, and monocytes, and the decrease in RBC, hemoglobin, hematocrit, and platelets. In the coagulation examination, an increase in Fbg concentration was noted. This change may be induced by the coagulase effect of the S. pseudintermedius, yet no effect on PT or APTT was noted, indicating the coagulation function has not been affected. In the clinical chemistry, the increase of creatine kinase and lactate dehydrogenase may indicate tissue cell damages. Significant increase of globulin may be caused by the inflammatory status. In conclusion, the findings in this case indicate that both Pseudomonas putida and Staphylococcus pseudintermedius can induce infections in laboratory beagle dogs under certain conditions, and might result in a fatal pneumonia which could progress very fast within several days.